The Al-Sunnah Method in Protecting The Environment: Hadith Perspectives - Daud Rasyid; Aisyah Daud Rasyid; Sofiya Daud Rasyid; Bilal Daud Rasyid (Elkawnie: Journal of Islamic Science and Technology, 2023)
Abstract: This article studies the Sunnah (including what the Prophet is saying and conducting) regarding crucial global issues, namely the environment. Prophet Muhammad had given directions to humankind to maintain the environment (including earth, water, air, and living things) from any corrupted acts. The Hadith books contain information on these issues. This study uses a qualitative methodology with a descriptive approach, collecting hadiths on the environment and maintenance, accompanied by the views of classical and contemporary scholars. The findings indicate that Prophet had talked about contemporary global issues like water protection, living things protection, including protection of plants, tree planting and reforestation, prohibition of tree cutting, animal protection and the means for not harming them, earth and land protection, a special topic on reviving dead land, air protection, and prohibiting polluting the air. If the world had implemented these directives, there would not be a current catastrophic environmental condition.Abstrak: Artikel ini membahas tentang Sunnah (dalam arti: ucapan dan perbuatan) Nabi terkait isu global yaitu isu lingkungan. Nabi Muhammad SAW. sudah memberikan arahan kepada umat manusia untuk menjaga lingkungan (mencakup: bumi, air, udara dan makhluk hidup) dari berbagai tindakan yang merusak. Hal itu tertuang di dalam hadits-haditsnya yang masih dibaca oleh setiap orang hingga hari ini. Studi ini menggunakan metodologi kualitatif dengan pendekatan deskriptif, mengumpulkan hadits-hadits yang terkait dengan lingkungan dan cara memeliharanya, disertai pandangan ulama klasik dan kontemporer. Temuan penelitian ini, Nabi telah berbicara seputar isu global saat ini, seperti perlindungan air, makhluk hidup – termasuk tumbuhan, penanaman pohon, penghijauan hutan, larangan pemotongan pohon- perlindungan hewan, tindakan menyakitinya, perlindungan tanah, serta topik khusus tentang peremajaan tanah tandus, perlindungan udara, dan larangan mengotorinya. Andai dunia menerapkan arahan ini, niscaya tidak terjadi malapetaka yang menimpa lingkungan sekarang.